Ethanol steam reforming on Ni/CaO catalysts for coproduction of hydrogen and carbon nanotubes. (7th January 2019) - Quan, Cui; Gao, Ningbo; Wang, Huihui; Sun, Hongman; Wu, Chunfei; Wang, Xinxin; Ma, Zhengzhao
Summary: Catalytic steam reforming of ethanol is considered as a promising technology for producing H2 in the modern world. In this study, using a fixed‐bed reactor, steam reforming of ethanol was performed for production of carbon nanotubes (CNTs) and H2 simultaneously at 600°C on Ni/CaO catalysts. Commercial CaO and a synthetic CaO prepared using sol‐gel were scrutinized for ethanol's catalytic steam reforming. Analysis results of N2 isothermal adsorption indicate that the CaO synthesized by sol‐gel has more pore volume and surface area in comparison with the commercial CaO. When Ni was loaded, the Ni/CaO catalyst shows an encouraging catalytic property for H2 production, and an increase in Ni loading could improve H2 production. The Ni/CaO catalyst with sol‐gel CaO support has presented a higher hydrogen production and better catalytic stability than the catalysts with the commercial CaO support at low Ni loading. The highest hydrogen yield is 76.8% at Ni loading content of 10% for the Ni/sol‐gel CaO catalyst with WHSV of 3.32/h and S/C ratio of 3. The carbon formed after steam reforming primarily consists of filamentous carbons and amorphous carbons, and CNTs are the predominant type of carbon deposition. The deposited extent of carbon on the used Ni/CaO catalyst lessen upon more Ni loading, and the elongated CNTs are desired to be formed at the surface of the Ni/sol‐gel CaO catalyst. Thus, an efficient process and improved economic value is associated with prompt hydrogen production and CNTs from ethanol steam reforming.